ANALISIS FUNGSI MOTIVATOR WALI PEMASYARAKATAN TERHADAP NARAPIDANA DITINJAU DARI PERMENKUMHAM NOMOR M.01 PK.04.10 TAHUN 2007 TENTANG WALI PEMASYARAKATAN - Windi Febriatmoko, Nur Agung (Journal of Correctional Studies, 2025)
Correctional guardians are correctional officers whose duties are as facilitators, communicators and motivators for prisoners and children who are undergoing guidance at correctional institutions. This research aims to explain the motivator function of correctional guardians towards prisoners in accordance with regulations that have been made, namely Permenkumham number M.02 PK04. 10 of 2007. This research uses normative juridical legal methods with secondary data sources in the form of primary legal materials, namely the Minister of Law and Human Rights regarding correctional guardians which were collected by means of literature study. The research results show that correctional guardians play a very important role as motivators for prisoners because prisoners need a place to tell stories, express their feelings and ask for advice and raise the spirit of prisoners in undergoing coaching.